Neonatal resuscitation workshop for trainees in standardized medical residency training—a pilot practice in Shenzhen, China - Xu, Chenguang; Zhang, Qianshen; Xue, Yin; Yang, Yuqian; Chen, Yihua; Yan, Wenjie; Cheung, Po-Yin (Frontiers in Pediatrics, 2023)
Background: Neonatal resuscitation is an important skillset for clinicians attending deliveries. Accredited neonatal resuscitation training is not obligatory in most training centers of standardized medical residency programs before 2022 in China. We investigated the feasibility and effectiveness of neonatal resuscitation simulation training (neo-RST) in residents in Shenzhen, China. Methods: Four two-day neo-RST workshops were conducted in the University of Hong Kong-Shenzhen Hospital and Shenzhen Health Capacity Building and Continuing Education Center in 2020-2021. The workshops had Neonatal Resuscitation Program (NRP)® update, skill stations and simulation practice with debriefing. Each participant had the integrated skill station assessment (ISSA) at the end of workshop. Participants of workshops included residents of different disciplines and health care providers (HCPs) of neonatal and obstetrical departments. We compared demographic characteristics, neonatal resuscitation knowledge before training, ISSA overall and categorical scores on skill sets between residents and HCPs. Results: The residents group (n=48) had less working experience, less prior experience in neo-RST and lower neonatal resuscitation knowledge scores than those of HCPs group (n=48). After the workshop, residents had higher overall ISSA score than that of HCPs group. There was no significant difference in the numbers of participants scored <80% in residents and HCPs group. Regarding the categorical scores, residents scored significantly higher in preparation, ventilation, crisis resource management and behavioral skills but lower in appropriate oxygen use, when compared with the HCPs. Conclusion: Neo-RST for residents is feasible with promising short-term educational outcomes. Neo-RST could be implemented in standardized medical residency programs in China.